2005
DOI: 10.1002/bdd.481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a ginseng saponin metabolite compound K in rats

Abstract: The absorption, dose-linearity and pharmacokinetics of compound K, a major intestinal bacterial metabolite of ginsenosides, were evaluated in vitro and in vivo. Using the Caco-2 cell monolayers, compound K showed moderate permeability with no directional effects, thus suggesting passive diffusion. After intravenous dose (i.v.; 1, 2, and 10 mg/kg), no significant dose-dependency was found in Cl (17.3-31.3 ml/min/kg), Vss (1677-2744 ml/kg), dose-normalized AUC (41.8-57.8 microg.min/ml based on 1 mg/kg) and t1/2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 23 publications
4
82
0
Order By: Relevance
“…Considering the oral bioavailability of C-K is reported to be ϳ5% in rodents Paek et al, 2006), the current study demonstrated that the inhibition of P-gp should lead to significantly increased oral bioavailability of C-K. Our previous publication showed that the bioavailability of Rh2s, another active ginsenoside with a similar structure and also a solid substrate of P-gp, was increased from 1 to Ͼ30% by coadministering cyclosporine A in mice (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Considering the oral bioavailability of C-K is reported to be ϳ5% in rodents Paek et al, 2006), the current study demonstrated that the inhibition of P-gp should lead to significantly increased oral bioavailability of C-K. Our previous publication showed that the bioavailability of Rh2s, another active ginsenoside with a similar structure and also a solid substrate of P-gp, was increased from 1 to Ͼ30% by coadministering cyclosporine A in mice (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…Despite the demonstration of the in vivo biotransformation of ginsenosides to C-K, C-K itself was reported to have low oral bioavailability (ϳ5%) in rats Paek et al, 2006). The absorption mechanism of C-K is generally considered to be passive diffusion, because one study showed that there was no difference between bidirectional transports in Caco-2 cells .…”
Section: Introductionmentioning
confidence: 99%
“…1). Their structures were assessed using the proton and carbon nuclear magnetic resonance (NMR; 1 H-NMR, 13 C-NMR) spectrum method with a Fourier transform NMR spectrometer (Inova AS 400 MHz NMR system; Varian, Vernon Hills, IL, USA) and pyridine-d 5 …”
Section: Structural Identificationmentioning
confidence: 99%
“…These ginsenosides were previously reported to exhibit various biological activities, including anti-inflammatory activity [1] and antitumor effects (inhibition of tumor-induced angiogenesis and prevention of tumor invasion and metastasis) [2,3], but these naturally occurring ginsenosides are poorly absorbed along human intestinal tracts [4]. Previous studies demonstrated that protopanaxadiol-type ginsenosides such as Rb1, Rb2, and Rc are metabolized by intestinal bacteria after oral administration of their final derivative, 20-O-β-d-glucopyranosyl-20(S)-protopanaxadiol, also called compound K. Compound K, reported to be easily absorbed by the human body, is the genuine active form of protopanaxadiol-type saponins [5], and it has recently attracted increasing interest because of its intriguing biological actions. Compound K was demonstrated to induce tumor cell apoptosis, inhibit tumor metastasis, and restrain tumor invasion [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane inserts were moved to other wells containing the same volume of fresh medium every 15 minutes for 1 h. An aliquot (1 mL) of each sample was collected from the basolateral side and stored at −80 °C until LC/MS analysis. 4 The apparent permeability coefficients (P app ) were calculated according to the following Eq. (2): (2) where, P app is the apparent permeability coefficient in cm/s, dQ/dt is the permeability rate, A is the diffusion area of the monolayer (cm 2 ) and C 0 is the initial concentration of the CK.…”
mentioning
confidence: 99%